Precise Localization in Craniotomy With a Retrosigmoid Keyhole Approach: Microsurgical Anatomy and Clinical Study - Jian, Zhi-Heng; Sheng, Min-Feng; Li, Jia-Yan; Li, Yu; Weng, Zhi-Jian; Chen, Gang (Frontiers in Surgery, 2022)
Objective:We aimed to explore a method of precise localization within craniotomy based on skull anatomical landmarks via the suboccipital retrosigmoid approach. Method:Craniometric measurements were taken from 15 adult dry skulls and eight cadaver head specimens. We investigated the relationship between anatomical markers in the skull specimens. Craniotomy was verified in clinical surgery by evaluating the accuracy, safety, rapidity, and minimal invasiveness of the procedure. In the anatomical study, eight cadaveric heads underwent a simulated craniotomy using the suboccipital retrosigmoid approach. Result:No venous sinus injuries were observed. We found that the distances from the keypoint to the top point of mastoid groove were 16.80±0.61 mm (left) and 14.83±5.13 mm (right), respectively; the distances from the keypoint to the asterion were 19.03±2.56 mm (left) and 22.60±4.15 mm (right), respectively; and the distances from the keypoint to the mastoidale were 33.99±4.16 mm (left) and 32.78±6.40 mm (right), respectively. Within clinical application, 29 patients underwent craniotomy using the suboccipital retrosigmoid approach. The operative area was clearly exposed in all patients and the microsurgical anatomy of the intracranial region after the dura mater incision was satisfactory. No venous sinus ruptures were observed. The average craniectomy time was 27.02±0.86 min. The diameter of the bone window was 1.7-2.9 cm. Conclusion:We conclude that the center of the burr hole can be precisely oriented 12 mm vertically above the top point of the mastoid groove based on the line between the supraorbital margin and the upper edge of the external auditory canal. This method can ensure safe, accurate, and rapid craniotomy with good vision while avoiding injury to the venous sinus.